'Alien Qualities': Hanne Darboven – constructing time. Issue 2 (1st September 2013) - Lauder, Adam
Hanne Darboven's numerical practice fulfils Alain Badiou's definition of a new artistic configuration (albeit one that the philosopher does not foretell). Darboven's writing – like that of Isidore Ducasse – subverts ordinary thinking through the 'alien qualities' of mathematics. Yet, in Darboven's grammatical oeuvre, infinity emerges as a function of number's capacity to be thought simultaneously across an unlimited number of discursive series. Her art affirms the plasticity of number by dispersing numerical series across a continuous surface. These surface effects simultaneously recall the disjunctive temporality of the Aion described by Gilles Deleuze in The Logic of Sense (2004). Finally, Darboven's writing of number also reveals traces of broader social transformations that emerged during the 1960s in tandem with unprecedented advances in automation and computing: particularly neo-Taylorist and cybernetic approaches to the administration of workers' time. But crises in labour practices are appropriated by Darboven as techniques of subjectivization that the artist always subverts to her own ends.